Accelerated stability test of snakehead fish and kelulut honey ointment with CMC-Na as a binder - Wintari Taurina; Mohamad Andrie; Nur Firdiena Titian Ratu (Universitas Ahmad Dahlan, 2021)
The extract of snakehead fish (Channa striata) and kelulut honey (Heterotrigona itama) ointment was proven to have activity in wound healing. However, previous studies showed instability in the ointment as indicated by the occurrence of phase separation. This study used CMC-Na (Carboxymethyl Cellulose Sodium) with a concentration of 3% (F1), 4.5% (F2), and 6% (F3) as a binder. The stabilizer was added to increase the stability of the ointment preparation by binding to the aqueous phase and preventing it from leaving the ointment base. The test was carried out with the accelerated stability method at a temperature of 40° ± 2° C and a humidity of 75% ± 5% for 28 days. The evaluation includes organoleptic tests, homogeneity, spreadability, adhesion, and protection power. The results showed that CMC-Na increased the stability of the ointment. The data obtained show that the higher the CMC-Na concentration used, the higher the consistency and adhesion were, but the lower the spreadability of the preparation. The results of the average spreadability and adhesion power for formulation 1 were 5.09 cm and 1797.33 seconds, formulation 2 were 4.42 cm and 1798.33 seconds, and formulation 3 were 3.69 cm and 1799 seconds. The results of the One-Way ANOVA showed that all formulations experienced a significant decrease in adhesion and increase in spreadability during 28 days of storage. The best ointment that meets the physical stability criteria is shown by the CMC-Na 3% (F1) formulation, with a soft texture, homogeneous, a good spreadability (5-7 cm), a good adhesion (more than 4 seconds), and a good protective power for 28 days of testing.